Development of Android-based Augmented Reality Media on Vocabulary Mastery and Pronunciation in English Subjects of Junior High School Students - Al-Farisy, Qorinul Choir; Priawasana, Endra; Triwahyuni, Eges (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
The use of learning media in schools is a very concerning urgency. The background of the development of Android-based Augmented Reality media is to see the utilisation of learning media in junior high school. Researchers are developing Android-based Augmented Reality media which is the latest technology-based media with 3-dimensional elements, video, text and sound on English subjects in junior high school. The data collection technique in this study is to use a research and development questionnaire to produce Android-based Augmented Reality media that is feasible to use based on the assessment of media experts, material experts, English language subject teachers and student responses. This research uses the research and development (R&D) method. The development procedure follows the modified Borg and Gall procedure from Sugiono, namely 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design improvement, 6) Product trial, 7) Product revision, 8) Final product. The results of this assessment indicate that Android-based Augmented Reality media has excellent feasibility according to media experts got a percentage of 84.17%, material experts 85.4%, teacher assessment 96.25% and student response 87%, which means this learning media is feasible to use